THE COMPARISON OF THE INCIDENCE OF PAIN, SWELLING, AND JOINT STIFFNESS BASED ON AGE CATEGORY USING THE COPCORD CORE QUESTIONNAIRE SCREENING METHOD - Gista Laila Hidayatul Rofiah; Wahono, Cesarius Singgih Wahono; Pratama, Mirza (Universitas Brawijaya, 2025)
Musculoskeletal complaints are one of the health problems with the highest incidence. These complaints include joint pain, swelling, and limited joint movement associated with the presence of a degenerative process. The degenerative process that results in decreased regeneration of individual cells is supported by several other factors, such as intensity of physical activity, history of underlying disease, body mass index (BMI), and others. This study aims to determine the differences in the incidence of musculoskeletal complaints: joint pain, joint stiffness, and joint swelling in various age categories classified by decade in the Malang City community. Methodology: Cross-sectional approach with multistage random sampling of the population of Kauman Village, Klojen District, Malang City, from June 2023 to August 2023, with interviews regarding complaints of joint pain, joint stiffness, and joint swelling suffered using a validated adaptation questionnaire from WHO-ILAR COPCORD; COPCORD Core Questionnaire. The results of the study found that 32.14% of subjects aged 18-30 years, 14.29% of subjects aged 31-40 years, 19.64% of subjects aged 41-50 years, 16.43% of subjects aged 51-60 years, 10.71% of subjects aged 61-70 years, 6,79% of subjects aged 71-90 years. The results of the analysis using the Binary Logistic Regression Test showed that musculoskeletal complaints were sequentially compared with the age of 31-40 years with the greatest incidence at the age of 61-70 years (p = <0.001), then the age of 71-90 years (p = 0.001), age 51-60 years (p = 0.024), age 41-50 years (p = 0.235), age 18-30 years (p = 0.019) with negative association of odd ratio. Likewise, the incidence of joint pain was compared sequentially with the age of 31-40 years with the greatest incidence at the age of 61-70 years (p = <0.001), then the age of 71-90 years (p = 0.002), the age of 51-60 years (p = 0.024), the age of 41-50 years (p = 0.235) and the age of 18-30 years (p = 0.042) with negative association of odd ratio. Then the sequential swelling incidences were compared with the age of 31-40 years, with the greatest incidence at the age of 71-90 years (p = 0.022), then the age of 41-50 years (p = 0.409) and the age of 61-70 years (p = 0.418). And the last, the sequential joint stiffness incidences were compared with the age of 31-40 years with the greatest incidence at the age of 71-90 years (p = <0.001), then the age of 61-70 years (p = 0.006), the age of 51-60 years (p = 0.254) and the age of 41-50 years (p = 0.372). Conclusion: Differences in age categories lead to differences in the incidence of musculoskeletal complaints, particularly joint pain. Joint stiffness and swelling are more common in elderly age groups.